Condições de trabalho e exaustão emocional elevada em enfermeiros no ambiente hospitalar - Sacadura-Leite, E.; Sousa-Uva; Ferreira, S.; Costa, P.; Passos, A. M. (Revista Brasileira de Medicina do Trabalho, 2019)
Background: Healthcare workers are exposed to many different occupational stressors, some of which are related to their working conditions. While the experience of stress seems to depend on individual perceptions, some characteristics of inpatient units might influence the occurrence of emotional exhaustion among nurses. Objective: The aim of the present study was to identify characteristics of inpatient units which might be associated with high levels of emotional exhaustion among healthcare workers, nurses in this case. Methods: We conducted the present cross-sectional, exploratory and descriptive study with 108 nurses (83.8% female; average age 33 years old) allocated to inpatients units (wards and intensive care) at a university hospital in Portugal. We administered the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) emotional exhaustion subscale and collected the following data relative to the units to which the participants were allocated: 1) mortality rate; 2) number of deceased patients; 3) shortage of nurses compared to national standards; 4) occupancy rate; 5) proportion of elderly patients (>65 years old). Results: We found a positive relationship between high levels of emotional exhaustion among nurses and very high number of deceased patients (p=0.012), high fatality rate (p=0.036) and high proportion of elderly patients (p=0.025). Conclusion: Very high number of deceased patients, high proportion of elderly patients and high fatality rate in inpatients units were associated with high levels of emotional exhaustion among nurses. These findings suggest that characterizing the objective conditions of inpatient units seems to be an important aspect to be considered in psychosocial risk management programs.